PENDAMPINGAN MANAJEMEN PEMASARAN BERBASIS URBAN FARMING+ KEPADA PELAKU USAHA HIDROPONIK ORGANIK DI MAOSPATI MAGETAN - Fahmi Alamil Huda; Paramita Wisnuwardhani (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Limited marketing capability remains a critical constraint affecting the competitiveness and sustainability of small-scale organic hydroponic enterprises despite their adequate production capacity. This community service program aimed to strengthen the marketing management of Green House Maospati, Magetan, Indonesia, through the proposed Urban Farming+ empowerment model. The model integrates marketing management, product quality standardization, and business matching to improve enterprise competitiveness and expand institutional market access. The program adopted a Participatory Action Research approach consisting of need assessment, capacity building, product quality standardization, business matching, and monitoring and evaluation. The program improved the partner's marketing capability, strengthened product quality management, developed promotional media, and facilitated initial business linkages with Aston Hotel Madiun. The findings indicate that the Urban Farming+ empowerment model provides an effective and replicable approach for strengthening the competitiveness, market readiness, and long-term sustainability of organic hydroponic enterprises from an agricultural socio-economic perspective.